2018
DOI: 10.1038/s41598-018-25524-3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin decreases Warburg effect in cancer cells by down-regulating pyruvate kinase M2 via mTOR-HIF1α inhibition

Abstract: Warburg effect is an emerging hallmark of cancer cells with pyruvate kinase M2 (PKM2) as its key regulator. Curcumin is an extensively-studied anti-cancer compound, however, its role in affecting cancer metabolism remains poorly understood. Herein, we show that curcumin inhibits glucose uptake and lactate production (Warburg effect) in a variety of cancer cell lines by down-regulating PKM2 expression, via inhibition of mTOR-HIF1α axis. Stable PKM2 silencing revealed that PKM2 is required for Warburg effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 62 publications
3
103
0
Order By: Relevance
“…They showed that a decrease of PKM2 (mediated by curcumin or by targeted PKM2 silencing) significantly reduces aerobic glycolysis and is also consequential for cell survival. Curcumin's influence on PKM1 was not addressed, and the effect was not shown as cell-type specific [22]. We wanted to explore the effect of curcumin on both isoforms in four different cancer -originating cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that a decrease of PKM2 (mediated by curcumin or by targeted PKM2 silencing) significantly reduces aerobic glycolysis and is also consequential for cell survival. Curcumin's influence on PKM1 was not addressed, and the effect was not shown as cell-type specific [22]. We wanted to explore the effect of curcumin on both isoforms in four different cancer -originating cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqui et al have recently reported that curcumin downregulates PKM2 expression in cancer cells, consequently decreasing the Warburg effect. The PKM2 downregulation coincided with the inhibition of the mammalian target of rapamycin (mTOR) pathway and consequential downregulation of hypoxia-inducible factor 1-alpha HIF1α [22]. Previously, PKM2 transcription has been shown to be activated on PI3K/mTOR-mediated HIF1α induction [23].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Curcumin and its analogues are shown to be emerging as effective agents for the treatment of several malignant diseases such as cancer. Numerous studies have shown that curcumin and its preparations can inhibit tumors in almost all parts of the body, including head and neck, ovarian, skin and gastric cancers [15][16][17][18][19][20].…”
Section: Curcuminmentioning
confidence: 99%
“…Tumor cells as well as TEC heavily depend on glycolysis (Warburg effect) for their energy requirements. Curcumin, an extensively studied polyphenolic compound, decreases glycolysis via dowregualting key glycolytic enzyme PKM2 via inhibiting mTOR/HIF-1α [121]. It up-regulates the PTEN expression via miRNA-21, thereby negatively regulating the PI3K/AKT pathway that regulates survival and glycolysis [122].…”
Section: Plant Compounds Targeting Metabolism Regulating Mirnamentioning
confidence: 99%